Improving fine motor skills of special education students in Sandakan by using hot box - Hassan, Muhamad Fazri (Jurnal Pendidikan Bitara UPSI, 2019)
Fine motor skills are an imperative element in child’s development aspect. Lacking in the ability to master fine motor skills often affect the children’s quality of learning process. Children with difficulties in fine motor skills usually experience trouble in using their hands and fingers to hold, write, shape and et cetera. In addition, these students will also face challenges in their school activities. Hence, the purpose of this action research is to improve (i) fine motor skills (ii) eye-hand coordination (iii) attention span in learning of special needs students in Sandakan by using HOT Box. Laidlaw action research model (1992) is used to map the process of this action research and qualitative approach is utilized to gather data. There are 20 participants involved in this research. Occupational therapy approach known as HOT Box is used to achieve the targeted objectives in this research. The research has been conducted in 3 months period.